Rural industrial convergence, urbanization development, and farmers’ income growth – evidence from the Chinese experience - Juan Yang; Juan Yang; Lingming Chen; Yadong Zhang (Frontiers in Sustainable Food Systems, 2023)
Farmers’ income growth is a significant social problem, which has a bearing on the building of a moderately prosperous society in an all-round way. The convergence of rural industries based on agricultural development has become a meaningful way to solve the problem. The convergence of rural industries cannot be separated from the construction of urbanisation because the aggregation of population resources and the optimisation of industrial structures need the support of urbanisation. Based on the panel data of 29 provinces in China from 2004 to 2020, this paper makes an empirical study on the interaction between rural industrial agglomeration, urbanisation level, and farmers’ income using the theories of “intermediate role” and “threshold effect.” The results show that rural industrial agglomeration significantly affects farmers’ economic development, among which the eastern, western, and central regions have the most substantial positive effect. The level of urbanisation development is the mediating variable of the impact of rural industrial convergence on farmers’ income growth, which indirectly promotes farmers’ income growth, and the mediating effect is significant. Lastly, the level of urbanisation development is the threshold variable for the impact of rural industrial convergence on farmers’ income growth, and the coefficient of rural industrial convergence on farmers’ income growth is highest when the level of urbanisation is between 0.7960 and 0.8500. Therefore, in order to achieve sustainable growth in farmers’ operating income, wage income and financial transfer income, the country should give full play to the advantages of rural industrial integration, build a modernised industrial system for agriculture, expand the functions of agriculture in the secondary and tertiary sectors, and make good use of the policies that benefit the people in rural industrial development. At the same time, with the opportunity of county urbanisation, a rural industrial development system with the county as the centre of development has been established, guiding the rational flow and effective integration of urban and rural industrial resource elements and realising the integrated development of urbanisation and rural industry. Given the differences in industrial development in the eastern, central and western regions, the State should also promote rural industrial integration policies by stage, region and strategy to raise the level of farmers’ income.